Nutrient intake, meal timing and sleep in elite male Australian football players - Falkenberg, E.; Aisbett, B.; Lastella, M.; Roberts, S.; Condo, D. (Journal of Science and Medicine in Sport, 2021)
Objectives: To investigate the relationship between dietary intake, meal timing and sleep in elite male Australian football players. Design: Prospective cohort study. Methods: Sleep and dietary intake were assessed in 36 elite male Australian Football League (AFL) players for 10 consecutive days in pre-season. Sleep was examined using wrist activity monitors and sleep diaries. Dietary intake was analysed using the smartphone application MealLogger and FoodWorks. Generalised linear mixed models examined the associations between diet [total daily and evening (>6 pm) energy, protein, carbohydrate, sugar and fat intake] and sleep [total sleep time (TST), sleep efficiency (SE), wake after sleep onset (WASO) and sleep onset latency (SOL)]. Results: Total daily energy intake (MJ) was associated with a longer WASO [ ß = 3, 95%CI: 0.2-5; p = 0.03] and SOL [ ß = 5, 95%CI: 1-9; p = 0.01]. Total daily protein intake (g kg -1) was associated with longer WASO [ ß = 4, 95%CI: 0.8-7; p = 0.01] and reduced SE [ ß = -0.7 CI: -1.3 to -0.2; p = 0.006], while evening protein intake (g kg -1) was associated with shortened SOL [ ß = -2, 95%CI: -4 to -0.4), p = 0.02]. Evening sugar intake (g kg -1) was associated with shorter TST [ ß = -5, 95%CI: -10 to -0.6; p = 0.03] and WASO [ ß = -1, 95%CI: -2 to -0.3; p = 0.005]. A longer period between the evening meal consumption and bedtime was associated with a shorter TST [ ß = -8, 95%CI: -16 to -0.3; p = 0.04]. Conclusions: Evening dietary factors, including sugar and protein intake, had the greatest association with sleep in elite male AFL players. Future research manipulating these dietary variables to determine cause and effect relationships, could guide dietary recommendations to improve sleep in athletes.